Experimental evaluation of advanced beam tracking with CSI acquisition for 5G radio access - Tateishi, Kiichi; Kurita, Daisuke; Harada, Atsushi; Kishiyama, Yoshihisa; Itoh, Shoji; Murai, Hideshi; Schrammar, Nicolas; Simonsson, Arne; Okvist, Peter (IEEE International Conference on Communications (2003), 2017)
This paper presents indoor and outdoor experimental results on 4-by-8 single-user (SU)-multiple-input multiple-output (MIMO) multiplexing based on 730.5 MHz bandwidth transmission when applying carrier aggregation (CA) with 8 component carriers (CCs) in a 15 GHz frequency band in the downlink of 5G cellular radio access. Beam tracking with massive MIMO is implemented in a 5G testbed to support user mobility with a narrow beam. In addition, channel state information (CSI) acquisition functionality is implemented for the scheduler to select appropriate beams. Experimental results in an indoor multi-path rich environment show the gain up to 34 % with CSI acquisition compared to the case of without CSI acquisition in a line-of-sight (LoS) environment with high rank MIMO transmission. The results also show the gain up to 55 % with CSI acquisition compared to the case of without CSI acquisition in LoS conditions due to reflections by buildings.